On proper accretive extensions of positive linear relations - Arlinsky, Yu. M. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
A linear relation S is called a proper extension of a symmetric linear relation S if S ⊂ S ⊂ S*. As is well known, an arbitrary dissipative extension of a symmetric linear relation is proper. In the present paper, we establish criteria for an accretive extension of a given positive symmetric linear relation to be proper.